Comprehensive variant calling from whole‐genome sequencing identifies a complex inversion that disrupts ZFPM2 in familial congenital diaphragmatic hernia. Issue 4 (4th February 2022) - Nicholas, Thomas J.; Al‐Sweel, Najla; Farrell, Andrew; Mao, Rong; Bayrak‐Toydemir, Pinar; Miller, Christine E.; Bentley, Dawn; Palmquist, Rachel; Moore, Barry; Hernandez, Edgar J.; Cormier, Michael J.; Fredrickson, Eric; et al.
Abstract: Background: Genetic disorders contribute to significant morbidity and mortality in critically ill newborns. Despite advances in genome sequencing technologies, a majority of neonatal cases remain unsolved. Complex structural variants (SVs) often elude conventional genome sequencing variant calling pipelines and will explain a portion of these unsolved cases. Methods: As part of the Utah NeoSeq project, we used a research‐based, rapid whole‐genome sequencing (WGS) protocol to investigate the genomic etiology for a newborn with a left‐sided congenital diaphragmatic hernia (CDH) and cardiac malformations, whose mother also had a history of CDH and atrial septal defect. Results: Using both a novel, alignment‐free and traditional alignment‐based variant callers, we identified a maternally inherited complex SV on chromosome 8, consisting of an inversion flanked by deletions. This complex inversion, further confirmed using orthogonal molecular techniques, disrupts the ZFPM2 gene, which is associated with both CDH and various congenital heart defects. Conclusions: Our results demonstrate that complex structural events, which often are unidentifiable or not reported by clinically validated testing procedures, can be discovered and accurately characterized with conventional, short‐read sequencing and underscore the utility of WGS as a first‐line diagnostic tool. Abstract : As part of the Utah NeoSeq project, we used a research‐based, rapid whole‐genome sequencing (WGS) protocol to investigate the genomic etiology for a newborn with a left‐sided congenital diaphragmatic hernia (CDH) and cardiac malformations, whose mother also had a history of CDH and atrial septal defect. Using both a novel, alignment‐free and traditional alignment‐based variant callers, we identified a maternally‐inherited complex SV on chromosome 8, consisting of an inversion flanked by deletions. This complex inversion, further confirmed using orthogonal molecular techniques, disrupts the ZFPM2 gene, which is associated with both CDH and various congenital heart defects. Our results demonstrate that complex structural events, which often are unidentifiable or not reported by clinically validated testing procedures, can be discovered and accurately characterized with conventional, short‐read sequencing and underscore the utility of WGS as a first‐line diagnostic tool.